2020
DOI: 10.1101/2020.10.22.341784
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Histone H2A ubiquitination resulting from Brap loss of function connects multiple aging hallmarks and accelerates neurodegeneration

Abstract: Aging is an intricate process that is characterized by multiple hallmarks including stem cell exhaustion, genome instability, epigenome alteration, impaired proteostasis, and cellular senescence. While each of these is detrimental at the cellular level, it remains unclear how they are interconnected to cause systemic organ deterioration. Here we show that abrogating Brap, a BRCA1 associated protein, results in cellular senescence with persistent DNA double-strand breaks and elevation of histone H2A mono- and p… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
1
1

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(12 citation statements)
references
References 94 publications
(162 reference statements)
2
10
0
Order By: Relevance
“…Consistent with γH2A.X, 53BP1 and Brca1, the two essential molecules for DSB repair, were also upregulated in Nde1 -/and Nde1 -/-p53 -/than in WT and p53 -/cortical tissues (Figure 5C). Moreover, IB of cortical histone extracts not only confirmed the elevation of γH2A.X in the cortical tissue of Nde1 -/and Nde1 -/-p53 -/mice but also showed that the increased γH2A.X in Nde1 -/and Nde1 -/-p53 -/mice were predominantly penta-ubiquitinated (Figure 5D, E ), a characteristic DNA damage response that we observed in Brap cKO mice and postmortem brains of patients with Alzheimer's disease (Guo et al, 2020). These data together demonstrated that Nde1 LOF increased DSBs in adult cortical neurons.…”
Section: Nde1 Lof Results In Heterochromatin Instability and Dsbs In Neocortical Neuronssupporting
confidence: 72%
See 4 more Smart Citations
“…Consistent with γH2A.X, 53BP1 and Brca1, the two essential molecules for DSB repair, were also upregulated in Nde1 -/and Nde1 -/-p53 -/than in WT and p53 -/cortical tissues (Figure 5C). Moreover, IB of cortical histone extracts not only confirmed the elevation of γH2A.X in the cortical tissue of Nde1 -/and Nde1 -/-p53 -/mice but also showed that the increased γH2A.X in Nde1 -/and Nde1 -/-p53 -/mice were predominantly penta-ubiquitinated (Figure 5D, E ), a characteristic DNA damage response that we observed in Brap cKO mice and postmortem brains of patients with Alzheimer's disease (Guo et al, 2020). These data together demonstrated that Nde1 LOF increased DSBs in adult cortical neurons.…”
Section: Nde1 Lof Results In Heterochromatin Instability and Dsbs In Neocortical Neuronssupporting
confidence: 72%
“…Moreover, IB of cortical histone extracts not only confirmed the elevation of γH2A.X in the cortical tissue of Nde1 -/- and Nde1 -/- p53 -/- mice but also showed that the increased γH2A.X in Nde1 -/- and Nde1 -/- p53 -/- mice were predominantly penta-ubiquitinated (Figure 5D, E). The dual PTM of phosphorylation and ubiquitination of histone H2A.X is a characteristic DNA damage response that we observed in Brap cKO mice and postmortem brains of patients with Alzheimer’s disease(Guo et al, 2020). Therefore, heterochromatin aberrations resulting from Nde1 LOF can lead to genome instability and DSBs in adult cortical neurons with age-dependent progression and pathological impacts.…”
Section: Resultsmentioning
confidence: 79%
See 3 more Smart Citations